AKUNTABILITAS DANA DESA DALAM UPAYA PEMBERDAYAAN MASYARAKAT DAN PEMBANGUNAN DESA : STUDI KASUS DESA LAHA, KECAMATAN TELUK AMBON - MEIDYLISA PATTY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The allocation of village funds has been an important issue since the issuance of the LAW on village independence in 2016. This research aims to study more about the accountability of allocation of village funds and its influence on community empowerment and Village development. The method of analysis used is qualitative descriptive analysis with data retrieval techniques that are surveys and interviews. Research object in Laha Village, the Bay district of Ambon Baguala, Maluku.The results showed that the management of the village funds are normative and administrative has been implemented as it should but is substantive there is still error due to some factors such as accountability and transparency which is still weak where the village apparatus has not fully socialized the budget plan and programs to the community, still strong element of kinship in the process of allocation of village funds and community participation that lacks